Śrīmanta Kailāsavāsī Rāmacandrarāva Gopāḷarāva, urpha, Āpāsāheba Paṭavardhana Jamakhaṇḍīkara yāñcẽ caritra - Phāṭaka, Hari Dāmodara (Hari Dāmodara Phāṭaka, 1910)
Biography of Rāmacandrarāva Gopāḷarāva Paṭavardhana Jamakhaṇḍīkara, 1833-1897, Prince of Jamkhandi, former Princely State.